Zebrafish macrophage developmental arrest underlies depletion of microglia and reveals Csf1r-independent metaphocytes - Kuil, Laura E; Oosterhof, Nynke; Ferrero, Giuliano; Mikulášová, Tereza; Hason, Martina; Dekker, Jordy; Rovira, Mireia; van der Linde, Herma C; van Strien, Paulina Mh; de Pater, Emma; Schaaf, Gerben; Bindels, Erik Mj; et al. (eLife, 2020)
Macrophages derive from multiple sources of hematopoietic progenitors. Most macrophages require colony-stimulating factor 1 receptor (CSF1R), but some macrophages persist in the absence of CSF1R. Here, we analyzed mpeg1:GFP-expressing macrophages in csf1r-deficient zebrafish and report that embryonic macrophages emerge followed by their developmental arrest. In larvae, mpeg1+ cell numbers then increased showing two distinct types in the skin: branched, putative Langerhans cells, and amoeboid cells. In contrast, although numbers also increased in csf1r-mutants, exclusively amoeboid mpeg1+ cells were present, which we showed by genetic lineage tracing to have a non-hematopoietic origin. They expressed macrophage-associated genes, but also showed decreased phagocytic gene expression and increased epithelial-associated gene expression, characteristic of metaphocytes, recently discovered ectoderm-derived cells. We further demonstrated that juvenile csf1r-deficient zebrafish exhibit systemic macrophage depletion. Thus, csf1r deficiency disrupts embryonic to adult macrophage development. Zebrafish deficient for csf1r are viable and permit analyzing the consequences of macrophage loss throughout life.
Keywords: Receptors, Granulocyte-Macrophage Colony-Stimulating Factor; receptory faktoru stimulujícího granulocyto-makrofágové kolonie; langerhans cells; microglia; makrofágy; dánio pruhované; developmental biology; zebrafish; tyrosinkinasy; zvířata; proliferace buněk; hematopoiesis; Zebrafish Proteins; tyrosinkinasové receptory; metaphocytes; CSF1R; Zebrafish; Protein-Tyrosine Kinases; Receptor Protein-Tyrosine Kinases; Cell Proliferation; stanovení celkové genové exprese; macrophages; Microglia; mikroglie; proteiny dánia pruhovaného; Animals; Macrophages; Gene Expression Profiling